The Effect of Social and Economical Infrastructures on Direct Foreign Financing and Economical Growth in Asian Nominated Western and Eastern Countries - Simin Ghaderi; Dr. Nazar Dehmardeh (جغرافیا و آمایش شهری منطقه‌ای, 2013)
Direct foreign financing is considered as an important factor for economical growth and development, removing the gap of saving- investment, financing, transfer of technology, technical knowledge and modern managerial methods. The current research is tried to review the effect of macro-economical effects, particularly the effect of infrastructures on attracting direct foreign financing and economical growth in the Asian nominated western and eastern countries during time period of 1980-2011, therefore, dividing  infrastructures in to two social and economical parts has been reviewed.   The models used in this research, with respect to the conditions of Asian nominated countries, were simultaneously estimated by 2 SLS method in a four designed equations in an equation system. The results showed that social and economical infrastructures had the greatest impact on attracting direct foreign financing and economical growth in east Asian nominated companies in comparing with the western countries. So that the effect of social and economical infrastructures’ coefficients on the economical growth of the Asian eastern countries is 0.70 and 0.60 respectively, and the effect of the above coefficients on attracting direct foreign financing in the said countries is 0.19 and 0.25 respectively.